2006
DOI: 10.1108/00251740610707703
|View full text |Cite
|
Sign up to set email alerts
|

Using cointegration methods to estimate the interconnectedness of intangible strategic assets

Abstract: PurposeThe aim of this paper is to advocate and implement cointegration methods for the estimation of interconnectedness of service quality and customer loyalty as intangible strategic assets within management decision.Design/methodology/approachUsing longitudinal time series quarterly data on loyalty and service quality, the paper uses cointegration methods to empirically estimate the weight of interconnectedness of customer loyalty and service quality as intangible strategic assets.FindingsThe research evide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 49 publications
(66 reference statements)
1
8
0
Order By: Relevance
“…Teece (1986) suggested that firms should invest in complementary assets such as manufacturing, additional know-how, sales channels in a profitable manner when commercializing the invention. Similar to previous studies, the investment in complementary assets results in maximizing profits from inventions (Levin et al, 1987;Cohen et al, 2000;Rothaermel, 2001;James et al, 2013;Onyeaso and Johnson, 2006). Although previous observations support our result, our result is distinguished from previous studies.…”
Section: Value Capture Mechanismsupporting
confidence: 87%
See 2 more Smart Citations
“…Teece (1986) suggested that firms should invest in complementary assets such as manufacturing, additional know-how, sales channels in a profitable manner when commercializing the invention. Similar to previous studies, the investment in complementary assets results in maximizing profits from inventions (Levin et al, 1987;Cohen et al, 2000;Rothaermel, 2001;James et al, 2013;Onyeaso and Johnson, 2006). Although previous observations support our result, our result is distinguished from previous studies.…”
Section: Value Capture Mechanismsupporting
confidence: 87%
“…Also, a dominant position of value capture between leading firms and following firms is determined by complementary assets. Therefore, the firm with strengthened complementary assets can acquire much more benefits through innovation than competitors (Onyeaso and Johnson, 2006). If a leading firm that launches a new product or technology with more complementary assets than its competitors; it can reduce the possibility of competitors' free-ride.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Onyeaso and Johnson (2006) estimated the interconnectedness of intangible strategic assets (service quality and customer loyalty) using cointegration methods. The results supported the perception that service quality would produce repeat purchase behavior (as a measure of loyalty) and enhance organizational performance.…”
Section: Value Of Intangible Assetsmentioning
confidence: 99%
“…Customer loyalty is a strategic objective for managers (Cooil et al , 2007) and is considered an intangible strategic asset that will enhance organizational performance (Onyeaso and Johnson, 2006). Therefore, investigating its determinants has drawn continuous attention from researchers.…”
Section: Literature Review and Hypotheses Definitionmentioning
confidence: 99%